Exploring HMMR as a therapeutic frontier in breast cancer treatment, its interaction with various cell cycle genes, and targeting its overexpression through specific inhibitors - Shabir, Aisha; Qayoom, Hina; Haq, Burhan Ul; Abo Mansoor, Adel; Abdelrahim, Adil; Ahmad, Irshad; Almilabairy, Abdullah; Ahmad, Fuzail; Mir, Manzoor Ahmad (Frontiers in Pharmacology, 2024)
Among women, breast carcinoma is one of the most complex cancers with one of the highest death rates worldwide. There have been significant improvements in treatment methods but the early detection still remains an issue to be resolved. This study explores into the multifaceted function of Hyaluronan-Mediated Motility Receptor (HMMR) in breast cancer progression. HMMR's association with key cell cycle regulators (AURKA, TPX2 and CDK1) underscores its pivotal role in cancer initiation and advancement. HMMR's involvement in microtubule assembly and cellular interactions, both extracellularly and intracellularly, provides critical insights into its contribution to cancer cell processes. Elevated HMMR expression, triggered by inflammatory signals, correlates with unfavourable prognosis in breast cancer and various other malignancies. Therefore, recognizing HMMR as a promising therapeutic target, the study validates the overexpression of HMMR in breast cancer and various pan cancers and its correlation with certain proteins such as AURKA, TPX2, CDK1 through online databases. Further the pathways associated with HMMR were explored using Pathway Enrichment Analysis such as Gene Ontology, offering a foundation for the development of effective strategies in breast cancer treatment. The study further highlights compounds capable of inhibiting certain pathway which in turn would inhibit the upregulation of HMMR in breast cancer. The results were further validated via MD simulations in addition to molecular docking to explore protein-protein/ligand interaction. Consequently, these findings imply that HMMR could play a pivotal role as a crucial oncogenic regulator, highlighting its potential as an auspicious target for the therapeutic intervention of breast carcinoma.